2017
DOI: 10.3945/ajcn.116.148270
|View full text |Cite
|
Sign up to set email alerts
|

Associations of maternal macronutrient intake during pregnancy with infant BMI peak characteristics and childhood BMI1–3

Abstract: Background: Infant body mass index (BMI) peak characteristics and early childhood BMI are emerging markers of future obesity and cardiometabolic disease risk, but little is known about their maternal nutritional determinants. Objective: We investigated the associations of maternal macronutrient intake with infant BMI peak characteristics and childhood BMI in the Growing Up in Singapore Towards healthy Outcomes study. Design: With the use of infant BMI data from birth to age 18 mo, infant BMI peak characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
62
5
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 45 publications
(48 reference statements)
5
62
5
3
Order By: Relevance
“…Brion et al found an inverse relationship between third‐trimester total carbohydrate intake and fat mass at ages 9 and 11 years; fat mass z‐score decreased by 0.07 (95% CI −0.12, −0.02) standard deviations for every 50 g increase in carbohydrates. Conversely, Chen et al observed positive associations between second‐ and third‐trimester total carbohydrate intake and offspring BMI z‐scores at ages 2‐4 years, peak BMI (the highest point on the BMI curve between birth and 18 months), and average pre‐peak BMI velocity (linear velocity from birth to peak BMI). The observed positive associations were partially explained by the type of carbohydrates being consumed, specifically sugar .…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Brion et al found an inverse relationship between third‐trimester total carbohydrate intake and fat mass at ages 9 and 11 years; fat mass z‐score decreased by 0.07 (95% CI −0.12, −0.02) standard deviations for every 50 g increase in carbohydrates. Conversely, Chen et al observed positive associations between second‐ and third‐trimester total carbohydrate intake and offspring BMI z‐scores at ages 2‐4 years, peak BMI (the highest point on the BMI curve between birth and 18 months), and average pre‐peak BMI velocity (linear velocity from birth to peak BMI). The observed positive associations were partially explained by the type of carbohydrates being consumed, specifically sugar .…”
Section: Resultsmentioning
confidence: 95%
“…Conversely, Chen et al observed positive associations between second‐ and third‐trimester total carbohydrate intake and offspring BMI z‐scores at ages 2‐4 years, peak BMI (the highest point on the BMI curve between birth and 18 months), and average pre‐peak BMI velocity (linear velocity from birth to peak BMI). The observed positive associations were partially explained by the type of carbohydrates being consumed, specifically sugar . Other studies reported similar findings for prenatal sugar intakes.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations